Crop rotation and succession in soybean production systems: cover crop biomass, grain yield and revenue - Pacheco, Leandro Pereira; Kappes, Claudinei; Côrt, Andressa Selestina Dalla [UNESP]; da Silva, Rayane Gabriel; de Souza, Edicarlos Damacena; Guedes, Thaís Rodrigues Magalhães; Silva, Laércio Santos; Ratke, Rafael Felippe; Petter, Fabiano André; dos Santos Ferreira, João Henrique [UNESP]; Portugal, José Roberto [UNESP]; Silva, Ivan David Ferreira; et al. (Springer Nature, 2025)
Background and aimsIntercropping and cover cropping represent promising alternatives to enhance soybean yield, biomass production, and nutrient cycling within sustainable agricultural systems. This study evaluated the mid-term effects of crop rotations and successions integrating cover crops and/or intercropping on biomass production, nutrient accumulation, soybean grain yield, and economic returns.MethodsThe experiment had been established six years earlier (2007/08) and was conducted over three crop seasons (2013/14, 2014/15, and 2015/16) in a randomized block design with four replications and eight production systems. All treatments were managed under no-till (NT), except for MC1, which followed conventional tillage. Soybean was the main cash crop, combined with different cover crop arrangements: fallow succession (MC2), Pennisetum glaucum (CS1), Urochloa ruziziensis (CS2), maize (Zea mays, CS3), and three crop rotation systems including Crotalaria spectabilis, maize, and U. ruziziensis in varying sequences (CR1, CR2, CR3).ResultsDry matter (DM) production and nutrient accumulation were measured in the cover crops of each system. In addition, soybean grain yield, estimated animal stocking rate, and estimated meat production were determined to evaluate the net return. Systems CS2, CS1, and CR3 had the highest nutrient accumulation, soybean grain yield, and revenue.ConclusionsMC1 and MC2 were the lowest-performing treatments across the evaluated variables, whereas rotation/succession systems with cover crops or intercropping under no-till showed higher soybean grain yield, a consistent yield increase over time, and greater revenue.